The Effect of Goal Setting, Self Efficacy, Interest and Peer Support on Self Regulated Learning - Sanyoto, Barkah; Saloom, Gazi (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThis research aims to see whether goal setting, self-efficacy, interest and peer support altogether have impact on self-regulated learning of students of STSN. Research population is 328 students of first to fourth year of STSN, while the sample is 291 students which filtered using convenience sampling method. This is a quantitative research. Research validity is examined using Confirmatory Factor Analysis (CFA). Data is analysed using multiple regression analysis. The result shows that goal setting, self-efficacy, interest and peer support altogether have impact on self-regulated learning. Variables of intensity, course efficacy, and intrinsic orientation have significant impact on self-regulated learning. While variables of content, roommate efficacy, social efficacy, affected related valence, value related valence, intrinsic orientation, tangible, belonging, appraisal, and self-esteem are statistically not proven to have an impact on self-regulated learning. In particular, this research shows that peer support independently has no effect on self-regulated learning meanwhile previous research has shown the opposite. Further research needs to consider the utilization of operational language which culturally appropriate regarding questionnaire drafting. It is because the questionnaire with the basis of local culture will ignite appropriate response from the respondents.AbstrakPenelitian ini bertujuan untuk melihat apakah penentuan tujuan, efikasi diri, minat dan dukungan teman sebaya berpengaruh bersama-sama terhadap regulasi diri mahasiswa Sekolah Tinggi Sandi Negara. Populasi penelitian adalah 328 mahasiswa STSN sedangkan sampel berjumlah 291 mahasiswa dengan menggunakan tehnik sampling convenience. Validitas alat ukur dianalisis dengan menggunakan CFA sedangkan data riset dianaisis dengan tehnik regresi berganda. Hasil penelitian menunjukkan bahwa penentuan tujuan, efikasi diri, minat dan dukungan teman sebaya secara bersama-sama berpengaruh terhadap regulasi diri mahasiswa. Secara khusus riset ini menunjukkan bahwa dukungan teman sebaya tidak berpengaruh terhadap regulasi diri mahasiswa, artinya, riset ini berbeda  dengan hasil riset terdahulu yang menunjukkan bahwa dukungan teman sebaya berpengaruh terhadap regulasi diri. Penelitian lebih lanjut perlu mempertimbangkan penggunaan bahasa operasional yang sesuai dengan budaya terkait penyusunan kuesioner. Pasalnya, kuesioner yang berbasis budaya lokal akan memicu respon yang tepat dari responden.How to Cite: Sanyoto, B., Saloom, G. (2020).   The Effect of Goal Setting, Self Efficacy, Interest and Peer Support on Self Regulated Learning. TARBIYA: Journal of Education in Muslim Society, 7 (1), 88-101. doi:10.15408/tjems.v7i1.13760.